La memoria viva y doña Dolores un personaje inspirado en las tradiciones (2024)
This investigative work is based on the creation of the traditional character "Doña Dolores" for the interdisciplinary play "Travesías para una romería". This creation is grounded in the Artistic Pedagogical Experience regarding the Current State of Tradition and the living memory of the author’s grandmother, through the exploration of the cultural traditions of the Promeseros Festival in Tibirita, Cundinamarca, and the